An artificial intelligence-enabled crop recommendation system - Uddin, Raiyan; Barua, Mrinmoy; Kabir, Mohammed Hossain; Nufayel, Muhammed; Sajid, Abu Sadman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.